Factors influencing permafrost temperatures across tree line in the uplands east of the Mackenzie Delta, 2004–2010 1 This article is one of a series of papers published in this CJES Special Issue on the theme of Fundamental and applied research on permafrost in Canada. 2 Polar Continental Shelf Contribution 03611. - Palmer, M.J.; Burn, C.R.; Kokelj, S.V. (Canadian Journal of Earth Sciences, 2012)
Air and near-surface ground temperatures, late-winter snow conditions, and characteristics of the vegetation cover and soil were measured across the forest–tundra transition in the uplands east of the Mackenzie Delta, Northwest Territories, in 2004–2010. Mean late-winter snow depth decreased northward from 73 cm in the subarctic boreal forest near Inuvik to 22 cm in low-shrub tundra. Annual near-surface ground temperatures decreased northward by 0.1–0.3 °C/km near the northern limit of trees, in association with an abrupt change in snow depth. The rate decreased to 0.01–0.06 °C/km in the tundra. The freezing season is twice as long as the thawing season in the region, so measured differences in the regional ground thermal regime were dominated by the contrast in winter surface conditions between forest and tundra.